GENETIC CHARACTERISTICS OF LONG-TAILED PARAKEETS (Psittacula longicauda modesta Fraser, 1845) FROM ENGGANO ISLAND - Adipraja Mahmuda; Jarulis; Dwi Astuti (BIOTROPIA, 2026)
ARTICLE HIGLIGHTS- Genetic variation found in long-tailed parakeets native to Enggano Island- Genetic information shows population differences among island parakeets- Enggano Island population displays unique genetic characteristics- Results support conservation efforts for long-tailed parakeets on Enggano IslandABSTRACTThe Enggano Long-tailed Parakeet is considered as an agricultural pest by farmers on Enggano Island, leading to a continuing decline in its wild population. This study investigated the genetic characteristics, nucleotide composition, single-nucleotide polymorphisms (SNPs), species-specific barcodes, genetic distances, and phylogenetic relationships of this subspecies using the mitochondrial cytochrome oxidase subunit I (COI) gene. Fourteen blood samples were collected from community-owned captive birds. Total genomic DNA was extracted using the DNeasy® Blood and Tissue Kit following the Qiagen Spin-Column Protocol. DNA amplification was performed by Polymerase Chain Reaction (PCR) using specific primers at the Zoology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Bengkulu. The amplified DNA was separated on a 2.4% agarose gel and visualized under ultraviolet light. Samples displaying clear DNA bands were subsequently sequenced by Apical Scientific. Sequence data were processed and aligned using MEGA version 11.0, resulting in a 665 bp COI fragment suitable for analysis. A total of 19 SNPs and 12 species-specific barcode sites were identified, indicating a distinct genetic signature in the Enggano population. Conserved sites were highly dominant (97.14%), while variable sites accounted for only 2.86%. Nucleotide composition analysis revealed a higher GC content (50.50%) than AT (49.47%). Genetic distance analysis showed 6 – 11.3% divergence between Psittacula longicauda modesta and other Psittacula species. Phylogenetic reconstruction placed all Enggano individuals in a well-supported monophyletic cluster (bootstrap value = 100), confirming their genetic separation from other parakeet species. These findings indicate low genetic diversity within the Enggano population, likely resulting from geographic isolation and small population size. The identified barcode sites underscore the strong diagnostic potential of the COI gene for molecular identification and taxonomic differentiation. Overall, this study establishes the first genetic baseline for Psittacula longicauda modesta, expands molecular resources available for the genus Psittacula, and provides valuable insights for conservation planning and taxonomic assessment of this endemic subspecies.